An Intelligent Neural Network Algorithm for Uncertainty Handling in Sensor Failure Scenario of Food Quality Assurance Model - Deepa, S.N.; Jayalakshmi, N. Yogambal (Computer Assisted Methods in Engineering and Science, 2022)
The quality of food is usually tested by sensing the product odor using e-nose technique. However, in a real-time testing environment, some of the employed sensors may fail to operate, which imposes great uncertainty on the food quality assurance model. To handle the uncertainty, a support vector machine (SVM) classifier algorithm is developed to deal with the failure sensor effect using a data imputation strategy. The proposed model is evaluated experimentally by means of benchmark datasets, and validated in a realtime environment by programming an Arduino-UNO controller in the internet of things (IoT) environment.